Number 44 (November 2002) - Southern Fishes Council (Southeastern Fishes Council Proceedings, 2002)
(November 2002) - Seasonal, diel and spawning habitat of the rare muscadine darter (Percina sp.) in the Conasauga River, Georgia. By Carol E. Johnston, Kevin J. Kleiner, and Steven J. Herrington The rediscovery of the Mississippi silverside, Menidia audens, in the Pearl River draninage in Mississippi and Louisiana. By Royal D. Suttkus and Bruce A. Thompson News and Notes
Keywords: seasonal; diel; spawning; fishes; habitat; rare; muscadine darter; percina sp.; conasauga river; mississippi silverside; menidia audens; pearl river drainage